Measuring the impact of the challenges of adopting blockchains for banking accounting on Syrian banking performance - خيربك أحمد (Latakia University Journal - Economic and Legal Sciences Series, 2025)
The aim of the research is to explore the challenges faced in adopting blockchain accounting, as well as the factors that may contribute to this adoption in the Syrian environment. This is particularly relevant given the observed weakness in adoption capabilities due to limited resources at some banks, especially in light of the rapid digital transformation being experienced across various sectors within the Syrian context. Thus, the goal of the research is to measure the reality of adoption challenges and indicate their highest levels, while assessing the impact of these challenges on the performance of Syrian banks. The research employed a descriptive analytical approach, and the questionnaire was directly distributed to employees in the accounting departments of public and private Syrian banks, yielding 62 responses suitable for analysis. The results indicated no statistically significant effect from economic, technological, organizational, or environmental challenges on banking performance. However, there is a statistically significant positive effect of the level of compatibility challenges of blockchain accounting with banks and the quality of blockchain accounting technology outputs on banking performance. The researcher recommends working to overcome compatibility challenges by providing the necessary infrastructure and equipment in order to achieve the highest level of output quality and improve banking performance, as demonstrated in the regression equation. Additionally, efforts should be made to address economic, technological, environmental, and organizational challenges, even though they did not show a direct effect on banking performance, due to their importance in developing banking operations, as they indirectly contribute to improving service quality.